Workplace violence against nurse: a systematic review and meta-analysis in Ethiopia - Sadik Abdulwehab; Frezer Kedir (BMC Nursing)
Abstract Background Workplace violence is a global public health concern, especially in developing nations. Nurses, due to the nature of their professional duties, often face an elevated risk of workplace violence. This risk is further exacerbated by the lack of adequate safety precautions and the presence of multiple potential perpetrators, making the work environment particularly hazardous for them. Objectives This systematic review explores workplace violence against nurses in Ethiopia, its prevalence, causes, Perpetrators of violence in the Nurses’ profession, consequences, influence on the profession, and strategies to prevent incidents based on relevant literature review. Review method and data sources The study sourced evidence from electronic databases like PubMed, Science Direct Scopus, Web of Science, and Google Scholar till January 30, 2024. The data was extracted from February 01–10 and later analyzed from February 15–March 15, and the report generation from March 15 to April 05, 2024, and reported findings per Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews. The study used pooled odds ratio and pooled proportion to assess exposure and outcomes. A meta-analysis was conducted using compressive met-analysis V4 packages, with forest plots for visual representation. Heterogeneity was evaluated using Cochran’s Q-test and I² statistic. Sensitivity analysis was performed by systematically excluding one study. Result In Ethiopia, workplace violence against nurses was a significant issue, with an incidence ranging from 26.7 to 64%. The most common form of violence was verbal abuse, followed by physical, psychological, and sexual harassment. Factors like age, gender, marital status, job type, work environment, and staffing levels contribute to the issue. Over half of nurses change shifts due to concerns about violence, community dissatisfaction, unsatisfactory treatment, and challenging nurse-patient relationships. Conclusion The prevalence of WPV among nurses in Ethiopia is increasing. Nurses face a high risk of workplace violence due to direct patient contact and the nature of the profession. Thus, healthcare organizations can work towards creating a safer and more supportive environment for nurses, enforce a zero-tolerance policy, improve patient-nurse relationships, and provide psychological support to ultimately reduce the prevalence of workplace violence and ensure the well-being of healthcare professionals. Prospero registration number CRD42024601317.